Transdermal Delivery of Glimepiride: A Novel Approach Using Nanomicelle-Embedded Microneedles - Sadia Pervez; Fazli Nasir; Talaya Hidayatullah; Muzna Ali Khattak; Fawaz Alasmari; Syeda Rabqa Zainab; Shazma Gohar; Arbab Tahir; Gul e Maryam (Pharmaceutics, 2023)
Glimepiride (GM) is a hydrophobic drug that dissolves slowly and yields inconsistent clinical responses after oral administration. Transdermal drug delivery (TDD) is an appropriate alternative to oral administration. Microneedles (MNs) offer a promising delivery system that penetrates the skin, while polymeric micelles can enhance the solubility; hence, the combination of both results in high drug bioavailability. This study aims to improve glimepiride’s solubility, dissolution rate, and bioavailability by incorporating nanomicelles into MNs for TDD. The nanomicelles formulated with 10% Soluplus® (SP) and 40% GM had a mean particle size of 82.6 ± 0.54, PDI of 0.1 ± 0.01, −16.2 ± 0.18 zeta potential, and achieved a 250-fold increase in solubility. The fabricated pyramid shaped GM-dissolving MNs were thermally stable and had no formulation incompatibility, as confirmed by thermal and FTIR analysis. The in vitro dissolution profile revealed that the GM release from nanomicelles and nanomicelle-loaded DMN was concentration-independent following non-Fickian transport mechanism. Improved pharmacokinetic parameters were obtained with dose of 240 µg as compared to 1 mg of GM oral tablet, in healthy human volunteers. The observed Cmax, Tmax and MRT were 1.56 μg/mL ± 0.06, 4 h, and 40.04 h ± 3.37, respectively. The safety profile assessment indicated that microneedles are safe with no adverse effects on skin or health. This study provides an alternative delivery system for the administration of glimepiride, resulting in improved bioavailability, enhanced patient compliance, and reduced dosing frequency.